Long-term decline of Acropora palmata (Scleractinia: Acroporidae) in San Andrés Island: 25 years of monitoring inside a Marine Protected Area - Pineda-Muñoz, Alexandra (2026)
Introduction: The condition of coral reefs in the Caribbean has deteriorated sharply over the past few decades, with Acropora palmata — historically a dominant reef-building coral — experiencing a regional decline of over 90 % due to the cumulative impacts of white band disease, hurricanes, and recurrent thermal stress. In response, Marine Protected Areas (MPAs) have been widely implemented across the region, yet their effectiveness in conserving vulnerable coral species remains uncertain. Objective: To document long-term trends in A. palmata cover at Little Reef, a secondary barrier reef located within the Seaflower MPAs surrounding San Andres Island, Colombia. Methods: Using standardized ecological monitoring protocols (CARICOMP, SIMAC, and years in which RRA was conducted), we analyzed coral cover based on five monitoring events (1995, 2002, 2006, 2021, 2024) spanning 29 years at a representative reef site in the Seaflower Biosphere Reserve. Results: Our results reveal a dramatic and statistically significant decline in A. palmata cover, from ~45 % total coral cover (dominated by A. palmata) in 1995 to just 1.13 % in 2024. The 2023 mass bleaching event led to near-complete mortality, with no visible signs of recovery observed during 2024 surveys. Statistical analyses confirmed a strong negative trend (Kendall’s Tau = –1.0, p = 0.017; R² = 0.865, p = 0.022), indicating sustained decline despite long-term protection. Conclusions: These findings reinforce growing evidence that MPAs alone may be insufficient to prevent coral loss under accelerating climate pressures. We highlight the need for conservation frameworks that combine passive protection with active restoration, climate-adaptive management, and genetic rescue approaches to safeguard A. palmata and other threatened reef-building species across the Caribbean.